2013
DOI: 10.1097/cad.0b013e32835cbde7
|View full text |Cite
|
Sign up to set email alerts
|

Preventing MEK1 activation influences the responses of human osteosarcoma cells to bone morphogenetic proteins 2 and 9

Abstract: It was recently suggested that bone morphogenetic protein (BMP)-2 may be useful for treating osteosarcoma cells. BMP-9, which has been patented to treat breast and prostate cancers, has a higher osteoinductive potential than BMP-2. Peptides derived from the knuckle epitope of BMPs (pBMPs) also induced osteogenic differentiation. However, the effect of BMP-9 and pBMPs on osteosarcoma cells is unclear. We analyzed the effects of BMP-2, BMP-9, pBMP-2, and pBMP-9 on the behavior of human MG-63 and SaOS-2 osteosarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Whether the effects observed in BMP-9-mediated osteogenic differentiation by ERK and p38 inhibition are the result of Smad signaling modulation or a direct effect of the MAPKs on this process is not known. Along these lines, p38 activation induced by BMP-9 has been documented in other cell types such as osteosarcoma cells [51], human osteoclasts derived from cord blood monocytes [52] and dental follicle stem cells [53]. In the former case, together with p38 activation, downregulation of phospho-ERK was achieved upon BMP-9 treatment.…”
Section: Bmp-9—non-smad Dependent Signalingmentioning
confidence: 98%
See 1 more Smart Citation
“…Whether the effects observed in BMP-9-mediated osteogenic differentiation by ERK and p38 inhibition are the result of Smad signaling modulation or a direct effect of the MAPKs on this process is not known. Along these lines, p38 activation induced by BMP-9 has been documented in other cell types such as osteosarcoma cells [51], human osteoclasts derived from cord blood monocytes [52] and dental follicle stem cells [53]. In the former case, together with p38 activation, downregulation of phospho-ERK was achieved upon BMP-9 treatment.…”
Section: Bmp-9—non-smad Dependent Signalingmentioning
confidence: 98%
“…Interestingly, Cox2 seems to directly modulate Smad1,5,8 signaling and Smad dependent gene expression in MPC [57]. Along these lines, the transcription factor Runx2, which is central for osteoblast differentiation by directly stimulating the expression of most of the well established bone markers (among them alkaline phosphatase and osteopontin), has been shown to be a target gene of BMP-9 in several cellular models like MPCs, osteosarcoma and dedifferentiated fat cells [51,56,58]. It is worth mentioning that the hypoxia inducible factor, Hif1α, has been recently described as a target of BMP-9 in MSC.…”
Section: Bmp-9 Mediated Regulation Of Target Gene Expressionmentioning
confidence: 99%
“…Recent studies analyzed the effect of BMP9 (rhBMP9 or AdBMP9) in different human osteosarcoma cell lines such as MG-63 cells [80,81]. For example, BMP9 expression was obtained through infection of human osteosarcoma MG-63 and 143B cells by a BMP9 expressing adenovirus [82].…”
Section: Bmp9 and Cancer Developmentmentioning
confidence: 99%
“…It has been hypothesized that the attractive osteogenic potential of BMP9 might be attributed to the differences in canonical BMP signaling pathways . Both BMP‐2 and −9 have been shown to activate SMAD pathways through the phosphorylation of the transcription factors Smad1/5/8 by type I receptors in osteoblast cells . Noggin is a well‐known BMP antagonist, which binds with carrying affinities and blocks SMAD‐dependent signaling.…”
Section: Discussionmentioning
confidence: 99%
“…7 Both BMP-2 and 29 have been shown to activate SMAD pathways through the phosphorylation of the transcription factors Smad1/5/8 by type I receptors in osteoblast cells. 34,35 Noggin is a wellknown BMP antagonist, which binds with carrying affinities and blocks SMAD-dependent signaling. Endogenous noggin also binds to BMP2 and inhibits its action whereas, previous reports have shown that BMP9 stimulation also leads to noggin expression, however SMAD phosphorylation by BMP9 is not inhibited.…”
Section: Discussionmentioning
confidence: 99%